2018
DOI: 10.1017/mor.2017.56
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Forces and Environmental Management Strategy: Moderating Effects of Environmental Orientation and Innovation Capability

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 140 publications
(314 reference statements)
1
49
0
1
Order By: Relevance
“…It is noteworthy to state that innovative practices and environmental innovative practices are used interchangeably. We juxtapose our findings with the findings of Kang and He (2018), Ruan, Hang and Wang (2014) and Yi, Hong, Hsu and Wang (2017) that unlike China, regulatory stakeholder pressures in India inhibit the adoption of sustainable practices with enduring focus and analyse the reasons thereof.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…It is noteworthy to state that innovative practices and environmental innovative practices are used interchangeably. We juxtapose our findings with the findings of Kang and He (2018), Ruan, Hang and Wang (2014) and Yi, Hong, Hsu and Wang (2017) that unlike China, regulatory stakeholder pressures in India inhibit the adoption of sustainable practices with enduring focus and analyse the reasons thereof.…”
Section: Introductionsupporting
confidence: 52%
“…The findings are incongruous with the claims of Menguc, Auh and Ozanne (2010) showing that government intervention may not be inhibiting. Moreover, an empirical study of the manufacturing firms operating in China also finds that institutional forces (i.e., regulative, public and industrial) positively influence the environmental management strategy (Kang & He, 2018). Furthermore, a meta‐analysis of 68 studies by Liu, Guo and Chi (2015) also conclude that in China, regulations have a significantly positive influence on proactive environmental strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite industry categories, there are several other elements that may affect the relationship between VER and CTI. For example, Kang and He () confirmed that corporate strategy orientation can influence the effect of VER on performance. Chang, Li, and Lu () believed that the innovation effect of VER is significantly related to governmental support.…”
Section: Discussionmentioning
confidence: 98%
“…Second, a high regulatory compliance capability enables a firm to take advantage of governmental inspection and to turn it into an opportunity to establish competitive advantage (Escobar & Chavez, ). Thus, possessing and effectively applying regulatory compliance capability will provide a firm with a potential avenue of differentiation through the adoption of a green innovation strategy (Kang & He, ).…”
Section: Literature and Hypothesesmentioning
confidence: 99%